A green body for eliminating high pressure forming ceramic sintering bulge and preparation method thereof

By optimizing the material of high-pressure molded ceramic body, reducing the amount of fusible hard raw materials and increasing the amount of refractory hard raw materials, the problem of sintering bulging defects of high-pressure molded ceramics has been solved, and product quality improvement and sustainable development have been achieved.

CN118754599BActive Publication Date: 2025-04-11HUIDA SANITARY WARE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410784692.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-04-11
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

High-pressure molded ceramic products are prone to sintering and bulging defects, and the existing technology has failed to effectively solve this problem, resulting in a decrease in product yield, an increase in production costs and waste of high-quality ceramic raw materials.

Method used

By optimizing the high-pressure molded sanitary ceramic body material system, the amount of large particles of fusible hard raw materials such as micro-plagiared feldspar and spodumene tailings is reduced, and the amount of refractory hard raw materials such as high-aluminum ceramic stone is increased, so that the raw materials particles can migrate in a direction under high pressure drive, the Al2O3 content in the center line is increased, the K2O and Na2O content is reduced, the refractory resistance is improved, the formation of vitrified liquid phase film is avoided, and the gas discharge is ensured.

Benefits of technology

It effectively controls the sintering bulging defects of high-pressure molded sanitary ceramic products, improves the refractory resistance and product quality of the blank, reduces the accumulation of industrial solid waste, and promotes the sustainable development of the sanitary ceramic industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754599B_ABST
    Figure CN118754599B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of sanitary ceramic production, and in particular to a green body and a preparation method thereof for eliminating sintering bulges of high-pressure formed ceramics. According to the percentage by mass of raw materials, the green body includes: 17%-25% kaolin, 0%-5% quartz, 5%-10% ball clay, 17%-27% high-aluminum porcelain stone, 0%-15% waste porcelain, 0%-15% low-glaze recycled mud, 0%-10% raw ore porcelain clay, 5%-20% washed porcelain clay, 10%-21% spodumene tailings and / or microcline, and 0%-7% wollastonite. The present invention accurately defines the formation and blocking mechanism of sintering bulges, and effectively controls the sintering bulge defects of high-pressure formed sanitary ceramic products; in addition, a large amount of industrial solid waste raw materials such as waste porcelain, waste mud, and spodumene tailings are also used in the green body formula of the present invention, which helps to reduce the accumulation of industrial solid waste, reduce environmental pressure, and promote the sustainable development of the sanitary ceramic industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sanitary ceramic production, in particular to a green body for eliminating sintering bulges of high-pressure formed ceramics and a preparation method thereof. Background Art

[0002] Sintering bulging (blistering) of the green body is one of the common product defects in the production of sanitary ceramics. Once it occurs, it will greatly affect the appearance and performance of the sanitary ceramic products. It cannot be eliminated by refiring (refiring, refiring), but will be further aggravated. Therefore, products with sintering bulging defects can only be scrapped, which seriously affects the yield of sanitary ceramic production, increases production costs, and causes waste of high-quality ceramic raw materials.

[0003] At present, it is generally believed in the ceramic industry that green body sintering bulging is mainly caused by three reasons: first, the green body sintering temperature range is too low, over-burning occurs, the green body is over-softened and produces more gas, resulting in sintering bulging; second, there are too many impurities such as carbonates, sulfates, and organic matter in the green body, and too much reaction gas is produced during the sintering process and cannot be discharged, resulting in sintering bulging; third, during the slip injection molding process, cavities appear in the green body, and the gas in the green body cavity expands at high temperature, resulting in sintering bulging. With the development of ceramic production technology, advanced testing methods such as X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma spectroscopy (ICP) can now efficiently and accurately determine the chemical composition of ceramic raw materials, conduct strict formula control, and ensure that the green body sintering range and impurity content meet production requirements; the green body cavity problem can also be effectively avoided by precise pressure control during the slip injection process. However, green body sintering bulging defects still often appear in double-sided slurry-eating sanitary ceramic products, especially high-pressure molding products. Obviously, the most important key factor causing green body sintering bulging has not yet been determined.

[0004] High-pressure molding is a new molding process that has become increasingly popular in the sanitary ceramics industry in recent years. Different from the traditional micro-pressure molding process, the mud is gradually dehydrated and molded through the capillary effect of the gypsum model under a low pressure of about 0.02MPa. The high-pressure molding process injects the mud into the resin model at a high pressure of about 1MPa, so that the water in the mud enters the micropores of the resin model and is quickly dehydrated and molded. Simple-structured sanitary ceramic products such as split toilets, smart toilet bases, squat toilets, and washbasins can be quickly molded through the high-pressure molding process, which greatly improves production efficiency. However, after sintering, the midline of the green body of the high-pressure molded product is very prone to bulging defects, such as Figure 1 As shown, the yield rate of high pressure forming products is seriously affected.

[0005] CN109824341A discloses a slurry and preparation method for reducing the defects of high-pressure forming re-fired bulging. By introducing a large amount of high-Al2O3 clay raw materials such as Zimujie clay and Henan clay, the amount of feldspar raw materials is reduced, and the overall refractoriness of the green body material is improved; the use of secondary grinding reduces the difference in particle size distribution of hard and soft materials, and alleviates the sintering bulging problem to a certain extent. However, since the refractoriness of the micro-area where the green body sintering bulging occurs is not accurately and effectively regulated, the green body sintering bulging problem is not fundamentally eliminated, and the overall improvement of refractoriness will cause the water absorption rate to exceed the national standard requirements; in addition, secondary grinding makes the slurry production process more complicated and energy consumption is also greater.

[0006] CN110078471A discloses a high-pressure grouting ceramic slurry and preparation method and system based on the recycling of waste porcelain. The particle size of waste porcelain particles in the slurry is reduced through secondary crushing and secondary grinding process, which alleviates the problem of green body bulging caused by high-pressure grouting stratification of large-particle waste porcelain. However, the relevant improvement measures are only for the waste porcelain, and no effective solution is formed to comprehensively solve the sintering bulging defect of high-pressure formed green body. And like CN109824341A, the secondary grinding complicates the production process and increases the production energy consumption.

[0007] Therefore, it is urgent to clarify the reasons why high-pressure formed products are prone to bulging defects, and to develop green bodies and preparation methods that can eliminate sintering bulges in high-pressure formed sanitary ceramics. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a green body and a preparation method thereof for eliminating sintering bulges of high-pressure formed ceramics, which effectively solves the problem that bulging defects are prone to occur in high-pressure formed ceramic products, and the various properties of the green body meet the production and use requirements of sanitary ceramics.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] In the first aspect, the present invention provides a green body for eliminating sintering bulges of high-pressure formed ceramics. Calculated by the mass percentage of raw materials, the green body includes: 17%-25% kaolin, 0%-5% quartz, 5%-10% ball clay, 17%-27% high-alumina porcelain stone, 0%-15% waste porcelain, 0%-15% low-glaze recycled mud, 0%-10% raw ore porcelain clay, 5%-20% washed porcelain clay, 10%-21% spodumene tailings and / or microcline, and 0%-7% wollastonite.

[0011] In some preferred embodiments, the green body includes, according to the percentage by mass of raw materials: according to the percentage by mass of raw materials, the green body includes: 20%-25% kaolin, 1%-3% quartz, 5%-8% ball clay, 18%-23% high-alumina porcelain stone, 3%-8% waste porcelain, 3%-10% low-glaze recycled mud, 0%-5% raw ore porcelain clay, 10%-15% washed porcelain clay, 15%-21% spodumene tailings and / or microcline, and 2%-5% wollastonite.

[0012] In some of the embodiments, the waste porcelain is ceramic particles obtained by crushing and removing iron from sanitary ceramic sintered products that fail quality inspection.

[0013] In some of the embodiments, the low-glaze recycled mud is waste mud containing a small amount of waste glaze generated in the production process of sanitary ceramics. The mud cake obtained after separate recovery, natural sedimentation and pressure filtration has a waste glaze content of less than 15%.

[0014] In some of the embodiments, the green body includes, calculated according to the mass percentage of the chemical composition of the raw materials, SiO2: 55%-60%, Al2O3: 24%-28%, Fe2O3: 0.5%-1.8%, TiO2: 0.5%-1%, CaO: 1%-2%, MgO: 0.2%-0.6%, K2O: 4%-4.5%, Na2O: 1%-1.5%, ZnO: 0%-0.4%, ZrO2: 0%-0.5%, Li2O: 0%-0.05%, and loss on ignition: 5%-10%.

[0015] In some of the embodiments, the sum of the mass percentages of SiO2 and Al2O3 is 80%-85%.

[0016] In some of the embodiments, the molar ratio of SiO2 and Al2O3 is (3.4-4.1):1.

[0017] In some of the embodiments, the molar ratio of K2O to Na2O is (2-2.8):1.

[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned green body for eliminating the sintering bulge of high pressure formed ceramics, comprising the following steps:

[0019] (1) Weigh the green body raw materials according to the proportion, add water and ball grind;

[0020] (2) grinding and sieving, adding water and additives to obtain slurry;

[0021] (3) The slurry is molded by high pressure grouting, dried and sintered to obtain the product.

[0022] In some of the embodiments, in step (1), the particle size distribution after ball milling is: D10≤3.5 μm, D50≤30.0 μm, D90≤100.0 μm.

[0023] In some embodiments, in step (2), the additive is one or more of water glass and alkaline noodles.

[0024] In some embodiments, in step (2), the concentration of the slurry is 350-360 g / 200 mL, and the yield value is 10-16 dyn / cm 2 The fluidity V0 is 45-70s / 200mL, and the pulp feeding speed is 6-9mm / 45min.

[0025] In some of the embodiments, in step (3), the grouting pressure is 0.8-1.2 MPa, and the maximum sintering temperature is 1200°C.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] During the research process, the inventors of the present application discovered that high-pressure formed ceramics are prone to sintering blistering because, during the high-pressure forming process of the sanitary ceramic body, the mud particles are driven by the grouting high pressure (about 1 MPa) to migrate from the center line toward the upper and lower slurry absorption surfaces of the resin model. The refractory clay raw materials with tiny particles migrate quickly, while the fusible hard raw materials with large particles (microcline, spodumene tailings, etc.) migrate slowly, thus forming a non-uniform chemical composition distribution of the body. The fusible feldspar raw materials gather near the center line. During the sintering process, a large amount of vitrified liquid phase is generated at the center line, forming a dense liquid phase film, which hinders the discharge of gas generated by the sintering reaction and leads to the problem of expansion and bulging of the body. In view of the above findings, the present invention optimizes the high-pressure formed sanitary ceramic body material system by appropriately reducing the amount of large-particle fusible hard raw materials such as microcline and spodumene tailings, and increasing the amount of refractory hard large-particle raw materials such as high-alumina porcelain stone. After the raw material particles migrate in a directional manner under high pressure, the Al2O3 content in the midline portion increases, the K2O and Na2O contents decrease, the refractoriness is improved, the amount of vitrified liquid phase generated in the midline portion during sintering is reduced, the formation of a dense liquid phase film is avoided, and the gas generated by the sintering reaction can be smoothly discharged from the body.

[0028] The present invention accurately defines the formation and blocking mechanism of sintering blister, and effectively controls the sintering blister defects of high-pressure formed sanitary ceramic products; in addition, the green body formula of the present invention also uses a large amount of industrial solid waste raw materials such as waste porcelain, waste mud, spodumene tailings, etc., which helps to reduce the accumulation of industrial solid waste, reduce environmental pressure, and promote the sustainable development of the sanitary ceramic industry.

[0029] The green body formula of the present invention can be applied to the existing preparation system, and the water absorption rate, sintering shrinkage, flexural strength and other properties of the green body obtained are close to those of the existing ordinary high-pressure formed green body, and the standard thickness deformation and deformation coefficient are relatively smaller, which is more conducive to product quality control; the green body formula of the present invention can meet the requirements of large-scale production of sanitary ceramic products, and the sintering bulging defect rate of the product is greatly reduced, which is suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 Optical photos of the bulge area of ​​high-pressure formed bulge defect sanitary ceramic products, including (a) front view; (b) cross section;

[0032] Figure 2 Schematic diagram of tiny particle migration during high pressure forming process;

[0033] Figure 3 This is a schematic diagram of the green body sintering bending deformation test;

[0034] Figure 4 The particle size distribution diagram of the green body centerline and the slurry absorption surface of Example 1 and Comparative Example 1;

[0035] Figure 5 The SEM photos of Example 1 (a) slurry absorption surface; (b) midline plane; (c) cross section and Comparative Example 1 (d) slurry absorption surface; (e) midline plane; (f) cross section;

[0036] Figure 6 The EDS test results of Example 1 (a) slurry absorption surface; (b) midline plane and Comparative Example 1 (c) slurry absorption surface; (d) midline plane;

[0037] Figure 7 This is the SEM-EDS test result diagram of the cracked area on the midline plane (inside the bulge) of Comparative Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0039] The chemical compositions of the raw materials used in the present invention and the comparative examples are shown in Table 1.

[0040] Table 1

[0041]

[0042] Example 1

[0043] A green body for eliminating high pressure formed ceramic sintering bulges is prepared by the following method:

[0044] (1) According to the mass percentage, 22% kaolin, 2% quartz, 6% ball clay, 20% high-aluminum porcelain stone, 5% waste porcelain, 5% low-glaze recycled mud, 5% raw ore porcelain clay, 15% washed porcelain clay, 17% spodumene tailings, and 3% wollastonite are mixed, and the raw materials are added with water and ground with high-aluminum balls until D10≤3.5μm, D50≤30.0μm, and D90≤100.0μm;

[0045] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 58.64% SiO2, 25.56% Al2O3, 1.44% Fe2O3, 0.62% TiO2, 1.58% CaO, 0.45% MgO, 4.21% K2O, 1.15% Na2O, 0.03% ZnO, 0.04% ZrO2, 0.03% Li2O, and 5.99% loss on ignition. The sum of the mass percentages of SiO2 and Al2O3 is 84.2%; the molar ratio of SiO2 to Al2O3 is 3.89:1; and the molar ratio of K2O to Na2O is 2.4:1.

[0046] (2) Grinding, sieving, adding water, 0.4% water glass and 0.1% alkaline surface relative to the total mass of the green body raw materials, to obtain mud, and controlling the mud concentration to 350g / 200mL and the yield value to 13dyn / cm 2 , fluidity V0 is 50s / 200mL, and pulp feeding speed is 8mm / 45min;

[0047] (3) The slurry is injected into a resin mold at a grouting pressure of about 1 MPa to form a ceramic green body after demoulding and drying. The green body is sintered in a tunnel kiln at a maximum sintering temperature of 1200° C. to obtain the green body. The sintering system is shown in Table 2.

[0048] Table 2

[0049]

[0050] Example 2

[0051] The preparation method of Example 2 is the same as that of Example 1, except that:

[0052] The green body comprises the following raw materials in terms of mass percentage: 22% kaolin, 2% quartz, 6% ball clay, 20% high-alumina porcelain stone, 5% waste porcelain, 10% low-glaze recycled mud, 15% washed porcelain clay, 17% spodumene tailings, and 3% wollastonite;

[0053] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 57.83% SiO2, 25.92% Al2O3, 1.45% Fe2O3, 0.63% TiO2, 1.74% CaO, 0.47% MgO, 4.13% K2O, 1.21% Na2O, 0.05% ZnO, 0.06% ZrO2, 0.03% Li2O, and 6.21% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 83.75%; the molar ratio of SiO2 to Al2O3 is 3.79:1; and the molar ratio of K2O to Na2O is 2.25:1.

[0054] Example 3

[0055] The preparation method of Example 3 is the same as that of Example 1, except that:

[0056] The green body comprises the following raw materials in terms of mass percentage: 22% kaolin, 2% quartz, 6% ball clay, 20% high-alumina porcelain stone, 10% waste porcelain, 10% low-glaze recycled mud, 10% washed porcelain clay, 17% spodumene tailings, and 3% wollastonite;

[0057] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 57.88% SiO2, 26.04% Al2O3, 1.41% Fe2O3, 0.64% TiO2, 1.83% CaO, 0.49% MgO, 4.13% K2O, 1.27% Na2O, 0.07% ZnO, 0.08% ZrO2, 0.03% Li2O, and 5.87% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 83.92%; the molar ratio of SiO2 to Al2O3 is 3.77:1; and the molar ratio of K2O to Na2O is 2.14:1.

[0058] Example 4

[0059] The preparation method of Example 4 is the same as that of Example 1, except that:

[0060] The green body comprises the following raw materials in terms of mass percentage: 23% kaolin, 6% ball clay, 20% high-alumina porcelain stone, 10% raw porcelain clay, 20% washed porcelain clay, 3% wollastonite, and 18% microcline;

[0061] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 58.74% SiO2, 25.47% Al2O3, 1.50% Fe2O3, 0.59% TiO2, 1.33% CaO, 0.41% MgO, 4.39% K2O, 1.08% Na2O, and 6.19% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 84.21%; the molar ratio of SiO2 to Al2O3 is 3.91:1; and the molar ratio of K2O to Na2O is 2.68:1.

[0062] Example 5

[0063] The preparation method of Example 5 is the same as that of Example 1, except that:

[0064] The green body comprises the following raw materials in terms of mass percentage: 17% kaolin, 2% quartz, 6% ball clay, 20% high-alumina porcelain stone, 15% waste porcelain, 15% low-glaze recycled mud, 4% raw porcelain clay, 4% washed porcelain clay, 14% spodumene tailings, and 3% wollastonite;

[0065] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 58.49% SiO2, 25.53% Al2O3, 1.36% Fe2O3, 0.67% TiO2, 2.09% CaO, 0.52% MgO, 4.16% K2O, 1.21% Na2O, 0.10% ZnO, 0.12% ZrO2, 0.02% Li2O, and 6.38% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 84.01%; the molar ratio of SiO2 to Al2O3 is 3.89:1; and the molar ratio of K2O to Na2O is 2.25:1.

[0066] Example 6

[0067] The preparation method of Example 6 is the same as that of Example 1, except that:

[0068] The green body comprises the following raw materials in terms of mass percentage: 22% kaolin, 6% ball clay, 27% high-alumina porcelain stone, 10% waste porcelain, 10% low-glaze recycled mud, 10% washed porcelain clay, 12% spodumene tailings, and 3% wollastonite;

[0069] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 55.17% SiO2, 27.97% Al2O3, 1.49% Fe2O3, 0.77% TiO2, 1.84% CaO, 0.53% MgO, 4.49% K2O, 0.99% Na2O, 0.07% ZnO, 0.08% ZrO2, 0.02% Li2O, and 6.31% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 83.13%; the molar ratio of SiO2 to Al2O3 is 3.35:1; and the molar ratio of K2O to Na2O is 2.99:1.

[0070] Example 7

[0071] The preparation method of Example 7 is the same as that of Example 1, except that:

[0072] The green body comprises the following raw materials in terms of mass percentage: 22% kaolin, 5% quartz, 6% ball clay, 17% high-alumina porcelain stone, 1% waste porcelain, 5% low-glaze recycled mud, 5% raw ore porcelain clay, 15% washed porcelain clay, 21% spodumene tailings, and 3% wollastonite;

[0073] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 60.70% SiO2, 24.02% Al2O3, 1.36% Fe2O3, 0.54% TiO2, 1.50% CaO, 0.41% MgO, 3.98% K2O, 1.33% Na2O, 0.02% ZnO, 0.03% ZrO2, 0.03% Li2O, and 5.82% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 84.73%; the molar ratio of SiO2 to Al2O3 is 4.29:1; and the molar ratio of K2O to Na2O is 1.97:1.

[0074] Comparative Example 1

[0075] Comparative Example 1 is a common high-pressure formed body widely used in the production of sanitary ceramics. Its preparation method is the same as that of Example 1, except that:

[0076] The common high-pressure forming body comprises the following raw materials in terms of mass percentage: 22% kaolin, 2% quartz, 6% ball clay, 12% high-alumina porcelain stone, 5% waste porcelain, 5% low-glaze recycled mud, 5% raw ore porcelain clay, 15% washed porcelain clay, 25% spodumene tailings, and 3% wollastonite;

[0077] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 61.22% SiO2, 23.67% Al2O3, 1.36% Fe2O3, 0.46% TiO2, 1.58% CaO, 0.4% MgO, 3.86% K2O, 1.61% Na2O, 0.03% ZnO, 0.04% ZrO2, and 5.49% ignition loss. The sum of the mass percentages of SiO2 and Al2O3 is 84.89%; the molar ratio of SiO2 to Al2O3 is 4.39:1; and the molar ratio of K2O to Na2O is 1.58:1.

[0078] Comparative Example 2

[0079] Comparative Example 2 is a high sodium high pressure formed body in which a part of the spodumene tailings is replaced by albite on the basis of the ordinary high pressure formed body formula. The preparation method is the same as that of Example 1, except that:

[0080] The high-pressure forming body comprises the following raw materials in terms of mass percentage: 20% kaolin, 2% quartz, 6% ball clay, 12% high-alumina porcelain stone, 5% waste porcelain, 5% low-glaze recycled mud, 7% raw ore porcelain clay, 15% washed porcelain clay, 15% spodumene tailings, 10% albite, and 3% wollastonite;

[0081] According to the percentage by weight of the chemical composition of the raw materials, the green body includes: 61.08% SiO2, 23.72% Al2O3, 1.34% Fe2O3, 0.46% TiO2, 1.59% CaO, 0.41% MgO, 3.54% K2O, 2.17% Na2O, 0.03% ZnO, 0.04% ZrO2, and 5.34% loss on ignition. The sum of the mass percentages of SiO2 and Al2O3 is 84.89%; the molar ratio of SiO2 to Al2O3 is 4.39:1; and the molar ratio of K2O to Na2O is 1.58:1.

[0082] Specifically, the compositions of the green body raw materials of Examples 1-7 and Comparative Examples 1-2 are shown in Table 3, and the chemical compositions of the green body raw materials are shown in Table 4.

[0083] Table 3 (Unit: %)

[0084]

[0085]

[0086] Table 4

[0087]

[0088] The relevant test methods and test equipment in Examples 1-7 and Comparative Examples 1-2 are as follows:

[0089] Particle size test: Japan Shimadzu Corporation, laser particle size analyzer (SALD-2201);

[0090] Sintering temperature test: Flow Corporation, USA, temperature measuring ring (BTC005, 900-1200℃);

[0091] Sintering shrinkage test: by comparing 10×20×250mm 3 The shrinkage rate of the rectangular test strip is calculated by the change in length before and after sintering, and the calculation formula is λ = (L0-L) / L0×100%. In the formula, λ is the linear shrinkage rate of the test strip; L0 is the length of the test strip before sintering; L is the length of the test strip after sintering.

[0092] Water absorption test: The water absorption of ceramic samples was tested using an electronic balance in accordance with ASTM C373-88 (2006).

[0093] Standard thickness deformation test: measuring 10×20×250mm 3 The deflection and thickness of the rectangular test bar after sintering on the refractory support with a span of 200mm are calculated by eliminating the influence of the thickness difference of the test bar and obtaining the bending deformation of the standard size test bar. The calculation formula is W = Sh 2 / 100, where W is the bending deformation, S is the deflection of the test bar after sintering, and h is the thickness of the test bar after sintering. Figure 3 .

[0094] Deformation coefficient test: measuring 10×20×250mm 3 The deflection and thickness of the rectangular test strip after sintering on the refractory support and the span of the refractory support are used to calculate the deformation coefficient of the green body material. The calculation formula is PI = 4Sh 2 / 3L 4 , where PI is the deformation coefficient, S is the deflection of the test bar after sintering, h is the thickness of the test bar after sintering, and L is the span of the refractory support.

[0095] Bending strength test: The universal material testing machine (AG-IS) of Shimadzu Corporation of Japan was used to test the three-point bending strength of a round bar-shaped test strip with a length of 120 mm and a diameter of 15 mm in accordance with the GB / T6569-2006 standard.

[0096] Chemical composition analysis: Bruker, UK, X-ray fluorescence spectrometry (XRF)

[0097] Phase analysis: Japan Rigaku Corporation, X-ray diffractometer (XRD).

[0098] Microstructure analysis: Field emission scanning electron microscope (SEM) from Zeiss, Germany.

[0099] Elemental composition analysis: Energy Dispersive Spectrometer (EDS) from Oxford, UK.

[0100] The performance test results of the green bodies prepared in Examples 1-7 and Comparative Examples 1-2 are shown in Table 5. During the trial production of Examples 1-7 and Comparative Examples 1-2, the sintering bulging defects of the trial-produced products were statistically analyzed and shown in Table 6.

[0101] Table 5

[0102]

[0103]

[0104] Table 6

[0105]

[0106] Combined with Table 5, by comparing Examples 1-7 with Comparative Examples 1 and 2, it can be seen that the water absorption rate, sintering shrinkage, and flexural strength of the green bodies of Examples 1-4 are close to those of the ordinary high-pressure formed green body of Comparative Example 1, and the standard thickness deformation and deformation coefficient are smaller than those of Comparative Example 1, which is more conducive to product quality control and can meet the requirements of large-scale production of sanitary ceramic products.

[0107] The standard thickness deformation, deformation coefficient and bulging defect rate of Examples 2 and 3 increase successively compared with Example 1. This is because the amount of low-glaze recycled mud and waste porcelain used in Examples 2 and 3 gradually increases, while the amount of original porcelain clay and washed porcelain clay gradually decreases compared with Example 1. Waste porcelain and low-glaze recycled mud contain more fusible components such as CaO, MgO, Na2O, ZnO, etc., the refractoriness of the green body decreases, the amount of glass phase generated during sintering increases, the bulging defects increase, and the deformation increases.

[0108] Example 4 does not use industrial solid waste raw materials such as low-glaze recycled mud, waste porcelain and spodumene tailings, and its performance is similar to that of Example 1, indicating that low-glaze recycled mud, waste porcelain and spodumene can be replaced with ceramic plastic clay raw materials, barren raw materials and flux, respectively. However, when industrial solid waste raw materials are not used, the formulation cost is high, which is not conducive to large-scale industrial promotion. Example 5 uses a large amount of industrial solid waste raw materials such as low-glaze recycled mud and waste porcelain, resulting in excessive fusible components such as CaO, MgO, Na2O, and ZnO in the green body derived from waste glaze and waste porcelain, and large deformation.

[0109] Example 6 uses more high-aluminum porcelain stone, the Al2O3 content of the green body is high, the molar ratio of SiO2 and Al2O3 is low, the molar ratio of K2O and Na2O is high, the refractoriness is high, it is not completely sintered, the water absorption rate is greater than 0.5%, and the strength is also low. In addition, the cost of high Al2O3 raw materials is high, the density of high Al2O3 green body is large, and the transportation cost is high, which is not conducive to large-scale industrial promotion; Example 7 uses less high-aluminum porcelain stone, the Al2O3 content of the green body is low, the molar ratio of SiO2 and Al2O3 is high, the molar ratio of K2O and Na2O is low, the refractoriness is low, the deformation is large, and it is difficult to meet the needs of sanitary ceramic product production and use.

[0110] Taking into account the water absorption rate, deformation, strength and cost of the blank, Example 1 is the optimal example.

[0111] Combined with Table 6, by comparing Examples 1-7 with Comparative Examples 1 and 2, it can be seen that the trial-produced products of Examples 1-4 and 6 have no blister defects after one-time firing, and the defect rate of blister after re-firing is also extremely low, while the defect rate of blister after one-time firing of Comparative Examples 1 and 2 is relatively high, reaching more than 1%, and the defect rate of blister after re-firing is even higher, exceeding 7%. This shows that by appropriately reducing the amount of large-particle fusible hard raw materials such as microcline and spodumene tailings, and increasing the amount of refractory large-particle hard raw materials such as high-aluminum porcelain stone, the refractoriness of the centerline of the green body can be improved, the amount of vitrified liquid phase generated in the centerline during the sintering process can be reduced, and the formation of a dense liquid phase film wrapped in gas expansion blister can be avoided, and the sintering blister defect can be almost completely eliminated.

[0112] The blister defect rate of Examples 5 and 7 in the first firing is slightly higher than that of Examples 1-4 and 6, and more blister defects also occur in the re-firing. This is because the amount of low-glaze recycled mud and waste porcelain used in Example 5 is large, and the fluxing components such as CaO and ZnO derived from waste glaze and waste porcelain in the green body are too high, which reduces the refractoriness of the midline part and easily forms a dense liquid phase film, resulting in sintering blister; the amount of high-aluminum porcelain stone used in Example 7 is small, resulting in lower refractoriness of the midline part than that of Examples 1-4 and 6. Therefore, the amount of vitrified liquid phase generated during the sintering process is larger, and it is easier to form a continuous liquid phase film to cause sintering blister defects. In addition, the blister defect rate of Examples 5, 7 and Comparative Examples 1 and 2 in the re-firing is significantly higher than that of the first firing, because the secondary sintering allows the liquid phase film encapsulating the gas in the midline part of the green body to be more fully formed, exacerbating the sintering blister problem.

[0113] At the same time, by comparing Comparative Example 1 and Comparative Example 2, it can be seen that the burn-back bulging defect rate of Comparative Example 2 is significantly higher than that of Comparative Example 1, and the difference between Comparative Example 2 and Comparative Example 1 is mainly that Comparative Example 2 adds hard large-grained albite raw materials with better fluxing effect than microcline and spodumene tailings. The increase of fusible hard large-grained albite leads to a higher Na2O content and lower refractoriness in the middle line part of the blank of Comparative Example 2, a larger amount of vitrified liquid phase is generated in the line part during sintering, and a dense liquid phase film is more easily formed, which hinders the discharge of gas generated by the sintering reaction, thereby causing an increase in the burn-back bulging defect rate of the blank.

[0114] The particle size of the powder taken from the center line and the slurry absorption surface of the green body of Example 1 and Comparative Example 1 was detected by a laser particle size analyzer. The particle size distribution curve is as follows: Figure 4 As shown in the figure, it can be seen that compared with the particle size distribution curve of the slurry absorption surface, the curve of the midline part is generally offset toward the high particle size direction, and the differential distribution curves of the two intersect at about 40μm. The large particles above 40μm in the midline part are significantly more than those on the slurry absorption surface, while the small particles are significantly less than those on the slurry absorption surface. This indicates that during the high-pressure molding process, the mud particles are driven by the grouting high pressure (about 1MPa) and migrate from the midline to the upper and lower slurry absorption surfaces of the resin model. The large particle raw material migrates slowly and is more distributed near the midline plane, while the small particle raw material migrates quickly and is more distributed near the slurry absorption surface, thus forming a non-uniform chemical composition distribution from the midline of the green body to the slurry absorption surface. This migration of tiny particles under high pressure is the physical process of bulge formation, such as Figure 2 shown.

[0115] The microscopic morphologies of the slurry absorption surface, midline plane and cross section of Example 1 and Comparative Example 1 were observed using a scanning electron microscope (SEM). Figure 5 As shown in the figure, it can be seen that the particles on the slurry absorption surface are finer and the pores are fewer, while the midline plane is obviously very rough and contains many large particles and pores. The cross-sectional electron microscope photo also shows a large number of pores concentrated in the midline. This further proves that after high-pressure forming, the large particles in the green body material system are more distributed near the midline. In addition, from Figure 5 (e) It can also be seen that there is obvious cracking in the midline plane (inside the bulge) of Comparative Example 1.

[0116] Figure 5 The elemental composition of the midline plane and the slurry absorption surface of Example 1 and Comparative Example 1 was tested by energy dispersive spectrometer (EDS) surface scanning. The results are as follows Figure 6As shown, it can be seen that the content of fusible components such as Na2O and K2O in the midline plane is significantly higher than that in the slurry absorption surface. This is caused by the slow migration speed of large-particle spodumene tailings / microcline raw materials rich in Na2O and K2O under high pressure. The aggregation of fusible components such as Na2O and K2O directly leads to a large amount of vitrified liquid phase generated in the midline part of the comparative example 1 during the sintering process, and it is easy to form a dense liquid phase film to encapsulate the gas, and the incidence of bulging defects is high. The midline plane of Example 1 contains more refractory Al2O3 components and less SiO2 and Na2O than that of comparative example 1, indicating that after using high-aluminum porcelain stone to replace spodumene tailings, a large amount of refractory hard large-particle high-aluminum porcelain stone with high Al2O3, low SiO2 and low Na2O is distributed near the midline, thereby significantly improving the refractoriness of the midline part of the green body, avoiding the formation of dense liquid phase film encapsulating gas expansion bulges during the sintering process, and eliminating the sintering bulge defects.

[0117] Comparative Example 1 The microscopic morphology and element composition of the cracked part inside the bulge were detected by SEM-EDS. Figure 7 As shown, it can be seen that the SiO2 content of positions ①-⑥ near the cracking part is relatively high, and the SiO2 content of positions ③, ④, and ⑥ is more than 80%, which indicates that there should be a large number of quartz crystals near the cracking part. The expansion coefficient of quartz crystals is relatively large. The parts where quartz crystals are concentrated will produce large deformation and tensile stress during the sintering and cooling process, leading to the occurrence of cracking. Since the SiO2 content of Example 1 is significantly lower than that of Comparative Example 1, the expansion coefficient is smaller, cracking is not likely to occur during the sintering and cooling process, and the mechanical properties are more stable.

[0118] Figure 7 Except for ③, ④, and ⑥ with extremely high SiO2 contents, the K2O and Na2O contents at positions ①, ②, and ⑤ are relatively high, indicating that the midline portion of the blank in Comparative Example 1 generally contains more glass phases, further proving that a large amount of vitrified liquid phase was generated at the midline portion during the sintering process of Comparative Example 1. Positions ③, ④, and ⑥ with extremely high SiO2 contents should be large quartz crystals, i.e. Figure 1 The bulges and burrs inside the middle bulge, although the content of K2O and Na2O in these areas is lower than that in other areas, still have considerable content, indicating that there is also glass phase attached to the surface, and the glass phase forms a continuous film in the midline of the green body. According to the EDS measurement depth, it can be determined that the thickness of the film is about several microns. During the sintering process, the formation of a continuous glass liquid phase film in the midline directly leads to the difficulty of exhausting the gas generated by the sintering reaction, and the green body expands and bulges.

[0119] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A green body for eliminating high pressure formed ceramic sintering bulges, characterized in that: According to the percentage by mass of raw materials, the green body comprises: 20%-25% kaolin, 1%-3% quartz, 5%-8% ball clay, 17%-27% high-alumina porcelain stone, 3%-8% waste porcelain, 3%-10% low-glaze recycled mud, 0%-5% raw porcelain clay, 10%-15% washed porcelain clay, 10%-21% spodumene tailings and / or microcline, and 2%-5% wollastonite; The green body is obtained through high-pressure grouting molding, drying and sintering.

2. The green body for eliminating high pressure formed ceramic sintering bulge according to claim 1, characterized in that: Calculated according to the weight percentage of the chemical composition of the raw materials, the green body includes: SiO2: 55%-60%, Al2O3: 24%-28%, Fe2O3: 0.5%-1.8%, TiO2: 0.5%-1%, CaO: 1%-2%, MgO: 0.2%-0.6%, K2O: 4%-4.5%, Na2O: 1%-1.5%, ZnO: 0%-0.4%, ZrO2: 0%-0.5%, Li2O: 0%-0.05%, and loss on ignition: 5%-10%.

3. The green body for eliminating high pressure formed ceramic sintering bulge according to claim 2, characterized in that: The sum of the mass percentages of the SiO2 and Al2O3 is 80%-85%; and / or the molar ratio of the SiO2 and Al2O3 is (3.4-4.1):

1.

4. The green body for eliminating high pressure formed ceramic sintering bulge according to claim 2, characterized in that: The molar ratio of K2O to Na2O is (2-2.8):

1.

5. The method for preparing a green body for eliminating high pressure formed ceramic sintering bulges according to any one of claims 1 to 4, characterized in that: The steps include: (1) Weigh the green body raw materials according to the proportion, add water and ball mill; (2) grinding and screening, adding water and additives to obtain slurry; (3) The slurry is molded by high-pressure grouting, dried and sintered to obtain the product.

6. The method for preparing a green body for eliminating high pressure formed ceramic sintering bulges according to claim 5, characterized in that: In step (1), the particle size distribution after ball milling is: D10≤3.5 μm, D50≤30.0 μm, D90≤100.0 μm.

7. The method for preparing a green body for eliminating high pressure formed ceramic sintering bulges according to claim 5, characterized in that: In step (2), the additive is one or more of water glass and alkaline noodles.

8. The method for preparing a green body for eliminating high pressure formed ceramic sintering bulges according to claim 5, characterized in that: In step (2), the concentration of the slurry is 350-360 g / 200 mL, and the yield value is 10-16 dyn / cm 2 The fluidity V0 is 45-70 s / 200mL, and the pulp feeding speed is 6-9 mm / 45min.

9. The method for preparing a green body for eliminating high pressure formed ceramic sintering bulges according to claim 5, characterized in that: In step (3), the grouting pressure is 0.8-1.2 MPa, and the maximum sintering temperature is 1200°C.

Citation Information

Patent Citations

  • Mud for reducing high-pressure forming and refiring swelling defects and preparing method

    CN109824341A

  • High-pressure grouting ceramic slurry based on waste ceramic recycling as well as preparation method and system

    CN110078471A

  • Low-temperature sintered sanitary ceramic green body and preparation method thereof

    CN113929437A